Wujud Partisipasi Masyarakat Suku Dayak Ma’anyan Dalam Penyelenggaraan Pendidikan Di SMA - Eshariyani Eshariyani (Jurnal Ilmiah Kanderang Tingang, 2023)
The aim of the research is to reach the undesrtanding participants of parents in raising the quality of leraning process education at elementary school,subtitial role and school management. The research design is qualitative approach its conduct at SMAN 1 Banua Lima in Tamiang Layang East Barito Central.Kalimantan.The method of the study is Comparative study using Fenomology approach. The research address at SMAN 1 Banua Lima at East Barito regency based on the recommendation from Education and Culture Drpartment of East Barito Regency. The research emphasized in participating of parents who mostly called as society of Dayak Ma'anyan in East Barito. The data collection gain by doing interviewing,observing and school documents.The interview has four stages. First Data condensation, second data mode,third data verification adnd four data conclusion. The result of the data meet that the participant of tje society who is parents from Dayak Ma'anyan support well to increase the quality of education for the students.The participation of parents implement in guiding the learning process for their children,controlling thr development personalization of their children,giving the facilities the children needs ,giving the evaluation of the school program,giving critical thinking controlling of the using school expenses and also giving the suggestion and collaborative ideas from.parents and the public figures societies.